Through-thickness texture gradient of tantalum sputtering target - Deng, Chao; Liu, Shi-Feng; Hao, Xiao-Bo; Ji, Jing-Li; Liu, Qing; Fan, Hai-Yang (Rare metals, 2017)
For sputtering targets, through-thickness texture is critical for assuring reliable sputtering performance.In this paper, through-thickness texture gradient of a rolled and subsequently annealed tantalum sputtering target was investigated. The results show that by carefully controlling the rolling process, shear-related components at the surface of the rolled sample could be avoided. Both the rolled sample and the annealed target develop a through-thickness texture gradient with the formation of a stronger {1 1 1}fiber in the center layer compared with that in the surface layer.